ANALISIS EFISIENSI SALURAN PEMASARAN IKAN LELE DI DESA RASAU JAYA 1 KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Imelda, Dani Apriono, Eva Dolorosa, (Jurnal Social Economic of Agriculture, 2012)
Abstract This study aims to determine the level of efficiency in the marketing channel catfish every marketing agencies. The method used is a survey method. Sampling was conducted with a random sample of respondents is simple. The number of samples in this study were 32 respondents catfish farmers while the sample population was taken marketing agency comprised of three retailers, 1 traders and 2 wholesalers. There are three marketing channels used in the Village pembudidaya Rasau Jaya Jaya District 1 District Rasau Fort Wayne to market catfish produced, ie (1) Pembudidaya-Retailer-Consumer, (2) Pembudidaya-Big Trader-Retailer-Consumer, (3) Pembudidaya-collectors-Great Traders-Retailer-Consumer. The entire marketing channel catfish has been efficient, but when seen from the comparison of margins and the farmer's share of the marketing channel I was most marketing channels efiesien. The marketing function is generally performed by a marketing agency involved in the marketing process is a function of exchange catfish and physical function. The cultivation of catfish farmers in the village do Rasau Jaya 1 is efficient to do, is seen from the value of the comparison between the reception and the R / C ratio of the total cost. Keywords: Efficiency of marketing, the marketing function, profit.